Common Regulators of Lipid Metabolism and Bone Marrow Adiposity in Postmenopausal Women - Dae-Yong Kim; Seong-Hee Ko (MDPI AG, 2023)
A variety of metabolic disorders are associated with a decrease in estradiol (E2) during natural or surgical menopause. Postmenopausal women are prone to excessive fat accumulation in skeletal muscle and adipose tissue due to the loss of E2 via abnormalities in lipid metabolism and serum lipid levels. In skeletal muscle and adipose tissue, genes related to energy metabolism and fatty acid oxidation, such as those encoding peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) and estrogen-related receptor alpha (ERRα), are downregulated, leading to increased fat synthesis and lipid metabolite accumulation. The same genes regulate lipid metabolism abnormalities in the bone marrow. In this review, abnormalities in lipid metabolism caused by E2 deficiency were investigated, with a focus on genes able to simultaneously regulate not only skeletal muscle and adipose tissue but also bone metabolism (e.g., genes encoding PGC-1α and ERRα). In addition, the mechanisms through which mesenchymal stem cells lead to adipocyte differentiation in the bone marrow as well as metabolic processes related to bone marrow adiposity, bone loss, and osteoporosis were evaluated, focusing on the loss of E2 and lipid metabolic alterations. The work reviewed here suggests that genes underlying lipid metabolism and bone marrow adiposity are candidate therapeutic targets for bone loss and osteoporosis in postmenopausal women.